STRATEGI PENANGGULANGAN BULLYING PADA SISWA DI SEKOLAH BERBASIS PESANTREN - Mistria Harmonis; Febri, Ach febri hasan (LPPM STAI Muhammadiyah Probolinggo, 2026)
Bullying in Islamic boarding schools remains a serious issue that requires comprehensive attention. The purpose of this study is to identify the types of bullying, the underlying reasons, and methods for addressing bullying in Islamic boarding schools, particularly at Raudlatul Muta'allimin Krejengan Junior High School in Probolinggo. The approach used in this study was descriptive qualitative, collecting data through in-depth interviews, participant observation, and documentation studies. Informants in this study included students, teachers, musyrif (leaders), and Islamic boarding school leaders who are directly involved in character development and student supervision. The study revealed that in Islamic boarding schools, there are four main types of bullying: verbal, physical, social, and religious. Causes include the existence of a senior-junior structure, strict rules without emotional attention, differences in socioeconomic status, a lack of emotional education, and minimal supervision from caregivers. Furthermore, a culture of violence, perceived as a means of discipline, also exacerbates bullying among students. Proposed strategies to address the problem include enhancing character education based on Islamic principles, strict supervision by caregivers and teachers, creating open communication spaces, and implementing a zero-tolerance policy against bullying. Furthermore, the active participation of all elements of the Islamic boarding school— kyai, ustadz, musyrif, senior students, and parents—is emphasized as a crucial factor in creating a safe, peaceful, and non-violent Islamic boarding school environment.